Nucleotide sequence of a cDNA clone encoding the entire glycoprotein from the New Jersey serotype of vesicular stomatitis virus. - Gallione, C J (1983)
The nucleotide sequence of the mRNA encoding the glycoprotein from the New Jersey serotype of vesicular stomatitis virus (VSV) was determined from a cDNA clone containing the entire coding region. The sequence of 12 5'-terminal noncoding nucleotides present in the mRNA but not in the cDNA clone was determined from a primer extended to the 5' terminus of the mRNA. The mRNA is 1,573 nucleotides long (excluding polyadenylic acid) and encodes a protein of 517 amino acids. Only six nucleotides occur between the translation termination codon and the polyadenylic acid. Short homologies between the untranslated termini of this mRNA and the mRNAs of the Indiana serotype were found. The predicted protein sequence was compared with that of the glycoprotein of the Indiana serotype of VSV and with the glycoprotein of rabies virus, using a computer program which determines optimal alignment. An amino acid identity of 50.9% was found for the two VSV serotypes. Approximately 20% identity was found between the rabies virus and VSV New Jersey glycoproteins. The positions and sizes of the transmembrane domains, the signal sequences, and the glycosylation sites are identical in both VSV serotypes. Two of five serine residues which were possible esterification sites for palmitate in the glycoprotein from the Indiana serotype are changed to glycine residues in the glycoprotein from the New Jersey serotype. Because the glycoprotein of the New Jersey serotype does not contain esterified palmitate, we suggest that one or both of these residues are the probable esterification sites in the glycoprotein from the Indiana serotype.